Biosynthetic Pathway and Metabolic Engineering of Succinic Acid - Liu, Xiutao; Zhao, Guang; Sun, Shengjie; Fan, Chuanle; Feng, Xinjun; Xiong, Peng (Frontiers in Bioengineering and Biotechnology, 2022)
Succinic acid, a dicarboxylic acid produced as an intermediate of the tricarboxylic acid (TCA) cycle, is one of the most important platform chemicals for the production of various high value-added derivatives. As traditional chemical synthesis processes suffer from nonrenewable resources and environment pollution, succinic acid biosynthesis has drawn increasing attention as a viable, more environmentally friendly alternative. To date, several metabolic engineering approaches have been utilized for constructing and optimizing succinic acid cell factories. In this review, different succinic acid biosynthesis pathways are summarized, with a focus on the key enzymes and metabolic engineering approaches, which mainly include redirecting carbon flux, balancing NADH/NAD+ ratios, and optimizing CO2 supplementation. Finally, future perspectives on the microbial production of succinic acid are discussed.